Age at type 2 diabetes diagnosis and the risk of mortality among US population - Hong-Jin Zhang; Jie Feng; Xiang-Tao Zhang; Hong-Zhou Zhang (Scientific Reports, 2024)
Abstract To examine the relationship between age at diagnosis of type 2 diabetes (T2DM) with cardiovascular and all-cause mortality in the U.S. population. Data was used from NHANES 1999 ~ 2018, which were screened to include a total of 8,654 participants with a diagnosis of diabetes for the study. We estimated the association between age at diagnosis and cardiovascular and all-cause mortality using weighted multivariate Cox regression analyses. Subgroup analyses and sensitivity analyses were performed to ensure the robustness of the data analysis. The number of participants diagnosed with diabetes at ages < 40, between 40 and 59, and > 60 are 1,492, 3,970, and 3,192, respectively, with median ages of 44.04, 57.59, and 72.24. Among patients diagnosed with T2DM, the relative risk of all-cause mortality increased with younger age at diagnosis: compared to patients with late-onset diabetes (age at type 2 diabetes diagnosis ≥ 60), the hazard ratio for all-cause mortality was 2.72 (95% CI 1.83–4.05) in those with early-onset diabetes (age at type 2 diabetes diagnosis < 40). Similarly, the risk of cardiovascular disease death was observed to be a higher relative risk with younger age at diagnosis. Exposure-effect analysis indicated that younger age at diagnosis is associated with higher risk of all-cause mortality. Subgroup analysis found that the association between age at diagnosis and cardiovascular and all-cause mortality was stronger in the current smokers and hypertensive population. The results of this study suggest that younger age at diagnosis of T2DM is associated with higher risk of death in patients. Younger patients diagnosed with T2DM had a higher risk of cardiovascular and all-cause mortality. These findings strengthen the understanding of the risk of death from T2DM and emphasize the importance of early prevention of diabetes.